2010
DOI: 10.1155/2010/542691
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Neurofilament Heavy Chain Correlations to Visual Function, Optical Coherence Tomography, and Treatment

Abstract: Objective. To correlate visual and neurologic clinical scores and treatment of optic neuritis and multiple sclerosis (MS) patients with assays of serum phosphorylated neurofilament heavy chain (pNF-H) and optical coherence tomography (OCT) measurements of axonal loss. Design/Methods. The Optic Neuritis Treatment Trial (ONTT) randomized 457 patients with acute optic neuritis to intravenous methylprednisolone (IVMP) followed by oral prednisone, oral prednisone or placebo treatment arms. We quantified serum pNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…This is consistent with the clinical observation of more server loss of visual function and retinal nerve fibres in patients with NMO [20]. Interestingly, loss of retinal nerve fibres as quantified by OCT was correlated to serum pNfH levels in patients participating in the Optic Neuritis Treatment Trial [11]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is consistent with the clinical observation of more server loss of visual function and retinal nerve fibres in patients with NMO [20]. Interestingly, loss of retinal nerve fibres as quantified by OCT was correlated to serum pNfH levels in patients participating in the Optic Neuritis Treatment Trial [11]. …”
Section: Discussionsupporting
confidence: 85%
“…Blood Nf heavy chain (NfH) levels have been shown to be elevated in patients with acute optic neuritis compared with control subjects, and its level correlates inversely with visual loss and the retinal nerve fibre thickness as assessed by retinal optical coherence tomography (OCT) [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, performance in the 9-HPT and its relationship with NfH levels was found predominantly in the non-dominant hand which may be related to the loss in manual dexterity that may be more obvious with the non-dominant hand as the test is normally performed faster using the dominant hand [13]. Others have also shown that high NfH levels correlate with poor visual outcome [14], [15]. Neuropsychological test scores from the PASAT and MSIS-29 appeared to be also responsive to changes in NfH, with patients with higher NfH having lower PASAT scores and higher MSIS-29 psychological scores, possibly related to the significant neurodegenerative changes observed in grey matter disease [16] or in relation to EDSS deterioration, respectively; McGuigan et al .…”
Section: Discussionmentioning
confidence: 99%
“…To date, plasma neurofilament heavy chain (NfH) levels have been shown to be raised in several central nervous system diseases, including amyotrophic lateral sclerosis (ALS) and optic neuritis . Neurofilaments are the most abundant neuronal cytoskeletal protein in peripheral nerves, and their concentration in blood likely reflects axonal breakdown and provides a biomarker of peripheral nerve disease .…”
mentioning
confidence: 99%